MOTIVASI INDONESIA MENDIRIKAN KONSULAT KEHORMATAN DI PALESTINA TAHUN 2016 - Bunga, Yuke; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study discusses or examines Indonesia's motivation to appoint Honorary Consulates in Palestine. Indonesia is one of the countries that establish diplomatic relations with many countries, one of which is Palestine. Indonesia's bilateral relationship with Palestine has long been established as Indonesia is one of the first prestigious Palestinian countries after the declaration of the Palestinian State in Algeria, November 15, 1988. The neo-realist approach used by the researchers to analyze this is considered suitable for the phenomenon being studied. The theory of neorealism (structural realism) is Kenneth Waltz's theory which is an attempt to overhaul the existing theory of realism. In this study using the concept of national interest. In achieving national goals by applying national goals there are factors that influence: interests, threats, capabilities and opportunities. The Government of Indonesia has established the Consulate of the Republic of Indonesia (RI) in Ramallah, Palestine. However the inauguration of the honorary consulate was not done in Ramallah, Palestine, sailor at the office of the Indonesian Embassy in Amman, Jordan. Konhor in Ramallah was opened by Foreign Minister Retno Marsudi on March 13, 2016. Kata Kunci: Motivasi, Konsulat Kehormatan, Palestina, Kemerdekaa